2020
DOI: 10.1192/j.eurpsy.2020.80
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of adolescents diagnosed with eating disorders and at risk for psychosis

Abstract: Background. The presence of subthreshold psychotic symptoms in adolescents with eating disorders is poorly described. This study provides a detailed characterization of adolescents affected by eating disorders in the absence or presence of subthreshold psychotic symptoms, taking into account a wide set of sociodemographic, psychological, and clinical variables. Methods. Ninety-four adolescents diagnosed with eating disorders were interviewed, focusing on clinical anamnesis and sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…It is also consistent with a large body of literature that emphasizes the causal role of body image processes in the generation of DE symptoms and behaviors (Dakanalis et al, 2016;Stice & Desjardins, 2018). Broadly in line with our findings, a study found that adolescents diagnosed with EDs and who were at risk for psychosis were more likely to report dysmorphophobia than their counterparts who screened negative for psychosis (Mensi et al, 2020). Body image concerns were reported as being among the most common psychotic features related to EDs (Stewart & Williamson, 2003;Zaider et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is also consistent with a large body of literature that emphasizes the causal role of body image processes in the generation of DE symptoms and behaviors (Dakanalis et al, 2016;Stice & Desjardins, 2018). Broadly in line with our findings, a study found that adolescents diagnosed with EDs and who were at risk for psychosis were more likely to report dysmorphophobia than their counterparts who screened negative for psychosis (Mensi et al, 2020). Body image concerns were reported as being among the most common psychotic features related to EDs (Stewart & Williamson, 2003;Zaider et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…When compared to the subgroup of students who were identified to be at risk for EDs from the self-report measures, patients reported a similar or higher frequency of positive endorsement of subclinical symptoms of psychosis (Miotto et al, 2010). Similarly, another Italian study found that attenuated psychotic symptoms were highly frequent in adolescents with EDs (84%); and that adolescents diagnosed with eating disorders who were identified as being at ultra-high risk (UHR) for psychosis reported higher EDs severity and experienced more frequently purging behaviors and dysmorphophobia as compared to non-UHR adolescents (Mensi et al, 2020). Scarcer still are studies on the topic involving the general population.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the CHR-P group showed a more significant presence of diagnoses of structuring personality disorder and bipolar symptoms. This group has many diagnoses of eating disorders [ 52 , 53 ]. In line with the literature [ 16 ], we found that the psychosis group had a massive presence of severe positive and negative symptoms compared to the other groups and was also the group with the lowest global functioning, the most compromised role and social functioning, and the most severe level of disorder severity based on clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive eating disorders (REDs) are serious mental disorders associated with potential medical complications stemming from malnutrition (Riva, Falbo, et al, 2022; Riva, Pigni, et al, 2022) and heightened psychiatric comorbidities (Mensi, Rogantini, et al, 2020; Momen et al, 2022), significantly impacting psychophysical health as well as social and family relationships (Herpertz‐Dahlmann, 2015). RED encompasses anorexia nervosa and atypical anorexia nervosa including both restrictive and binge‐purge subtypes (American Psychiatric Association, 2022).…”
Section: Introductionmentioning
confidence: 99%